Pelatian Microsoft Excel Untuk Meningkatkan Kompetensi Pengolahan Data Kepada Siswa/i di SMP Islam Darul Muwahhidin - Zaehol Fatah; Roy Hanul Wafa (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
Advances in information technology in today's digital era require extensive specialized training to develop digital literacy skills, one of which is the use of data processing applications such as Microsoft Excel. However, many junior high school students still lack a thorough grasp of Microsoft Excel. Therefore, this community service initiative is designed to improve students' digital skills through Microsoft Excel training at Darul Muwahhidin Islamic Junior High School. This activity was implemented in person through several stages: preparation, training, practice, discussion, and evaluation. The material taught included an introduction to the Microsoft Excel interface, the application of basic formulas such as SUM, COUNTIF, and AVERAGE, managing data tables, and creating simple graphs. The results of this activity showed that the students enjoyed the face-to-face training, receiving positive feedback from both the school and the students. Most students began to understand the basics of Microsoft Excel and were able to perform simple data processing tasks such as attendance and grade recaps. Participant satisfaction levels indicated that 60% of students had a good grasp of the material, and 20% were very satisfied with the training. This activity has had a positive impact on improving students' data processing skills, critical thinking skills, and interest in information technology. Therefore, this Microsoft Excel training serves as a tool for us to more effectively support students' digital literacy development in the modern era.